The Tragedy of the Holocaust in Lithuania: from the Roots of the Identity to the Efforts Towards Reconciliation - Gruodytė, Edita; Adomaitytė, Aurelija (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
The relationship of each State with the Holocaust is twofold. Each self-respecting and democratic State, which recognizes international human rights, makes all efforts that this painful period of history is known to the public and to future generations. Secondly, the perception of the holocaust directly depends on the individual relationship each society has with the tragedy of the criminal act. This means that education about the Holocaust should go beyond the simple integration of specific programmes into the system of a state education, but the success of such programmes is dependent on the fact of how the society in question treats the historical, political, social and legal context of the holocaust. No less important is an evaluation of the impact which the holocaust makes to the development of society and the state. It is established fact that, after the Nazi occupation, not only Germans but also native Lithuanians participated in the actions of the Holocaust. It is important that the collective memory about ethnical, religious and racial conflicts, touching the collective identity, honour, liability and unfairness, is transferred from generation to generation. It is necessary to understand the circumstances and causes which influenced or are still impacting the understanding of the holocaust tragedy with regard to the whole society or to the specific perception by separate individuals. Taking into account the mentioned circumstances, several main aspects which define the relationship of Lithuanian society with the holocaust are revealed. The first issue discussed in the article is the Jewish-Lithuanian relations until the Holocaust, as in many cases stereotypes about Jews which developed during that period continue to affect the understanding of the holocaust tragedy to this day. A second important factor discussed in the paper - that the holocaust did not involve just a tragedy of society or state, but it is also a personal drama of each individual who was involved in the atrocities of the holocaust, especially when it comes to collective responsibility. Moreover, the question of liability is complicated by the fact that at the time of the holocaust the surviving members of Lithuania's Jewish community, who had played an active and important part in Lithuanian society and who were almost exterminated, emigrated. Because of Soviet policies, the survivors who stayed in Lithuania were forced to deny their identity. After all, the holocaust is the field of various legal evaluations and interests. Contrary to the situation in Western Europe, in Lithuania like in other post-communist countries, the holocaust is treated not as some unique event, having no analogue phenomena, but is viewed together with the atrocities of the Soviet occupation. It follows that a pure and appropriate analysis regarding changes of the legal situation in Lithuania’s understanding of the Holocaust in the light of Soviet crimes should be carried out. It must be stated, that the authors of the article do not pretend to be analyzing the methods or the scale of Lithuanians’ participation in the Jewish genocide, or to be providing arguments to deny or justify their behavior. This article is an effort towards a better understanding of how the process of reconciliation between two nations (Lithuania and Israel) is influenced by specific historical and political conditions. It should be noted that the authors do not discuss and evaluate the scale of forced deportations in other countries as the main issue of the article is to find out the Lithuanian attitude to the matter.
Keywords: holocaust in Lithuania; Jewish identity; Nazi and Soviet crimes